PENGEMBANGAN MEDIA PEMBELAJARAN MYSTERY BOX BERBANTUAN QR CODE PADA MATERI SISTEM PENCERNAAN MANUSIA MATA PELAJARAN IPAS KELAS V SEKOLAH DASAR - Anggun Saptiani; Faizal Chan; Khoirunnisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the limited use of interactive learning media in science and social studies (IPAS), particularly in teaching the human digestive system in Grade V elementary school. Learning activities were still dominated by lectures and textbooks, resulting in low student engagement and difficulties in understanding abstract concepts. This research aimed to develop a Mystery Box learning media assisted by QR Code that meets the criteria of validity and practicality. The study employed a Research and Development (R&D) approach using the 4-D model (Define, Design, Develop, and Disseminate). The research was conducted at SD Negeri 182/I Hutan Lindung involving expert validators, teachers, and Grade V students. Data were collected through observation, interviews, validation questionnaires, and practicality questionnaires. The validation results indicated that the media was categorized as very valid, with a score of 96.66% from media experts, 96.66% from material experts, and 100% from language experts. The practicality test showed that the teacher’s response reached 94.28%, categorized as very practical. These findings demonstrate that the QR Code-assisted Mystery Box media is feasible and practical to be implemented in IPAS learning on the human digestive system topic in Grade V elementary school.